Optimisation of biodiesel production from mixed Sterculia foetida and rice bran oil - Kusumo F.; Mahlia T.M.I.; Shamsuddin A.H.; Ahmad A.R.; Silitonga A.S.; Dharma S.; Mofijur M.; Ideris F.; Ong H.C.; Sebayang R.; Milano J.; Hassan M.H.; et al. (Taylor and Francis Ltd., 2023)
Esters; Furfural; Potassium hydroxide; Transesterification; Bio-energy; Biodiesel production; Methyl esters; Non-edible oil; Optimisations; Process Variables; Rice bran oil; Rice brans; Sterculia foetida; Transesterification process; Biodiesel